2022
DOI: 10.1029/2022gl099039
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Near‐Surface Wind Speeds With Increasing CO2 May Worsen Winter Air Quality in the Indo‐Gangetic Plain

Abstract: We analyze the relationship between fine particulate matter (PM2.5) and meteorology in winter in the Indo‐Gangetic Plain (IGP). We find that the concentration of PM2.5 exhibits similar increase with decreasing surface wind speed in 15 out of 18 cities considered. Using this observed relationship, we estimate that the reduction of surface wind speed with increasing CO2 simulated by models participating in the Coupled Model Intercomparison Project Phase 6 will result in higher average wintertime PM2.5 concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 127 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…However, Gunturu and Kumar (2021) attributed the recent increases in wintertime fog over the Indo-Gangetic Plains to reduced WD activity, arguing that fewer WDs have led to reduced cloud cover and increased radiative cooling. Reduced WD frequency, and hence weaker near-surface winds and precipitation, has also been linked to increased pollution over north India, both in models (Paulot et al, 2022) and observations (Xie et al, 2023;Patnaik et al, 2024). The influence of WDs on air quality also extends to the Central Himalaya - Sundriyal et al (2018) showed that dust present in the Dokriani Glacier had come from arid regions like the Thar desert (see Fig.…”
Section: Fog Dust and Pollutionmentioning
confidence: 99%
“…However, Gunturu and Kumar (2021) attributed the recent increases in wintertime fog over the Indo-Gangetic Plains to reduced WD activity, arguing that fewer WDs have led to reduced cloud cover and increased radiative cooling. Reduced WD frequency, and hence weaker near-surface winds and precipitation, has also been linked to increased pollution over north India, both in models (Paulot et al, 2022) and observations (Xie et al, 2023;Patnaik et al, 2024). The influence of WDs on air quality also extends to the Central Himalaya - Sundriyal et al (2018) showed that dust present in the Dokriani Glacier had come from arid regions like the Thar desert (see Fig.…”
Section: Fog Dust and Pollutionmentioning
confidence: 99%
“…However, Gunturu and Kumar (2021) attributed the recent increases in wintertime fog over the Indo-Gangetic Plains to reduced WD activity, arguing that fewer WDs have led to reduced cloud cover and increased radiative cooling. Reduced WD frequency, and hence weaker near-surface winds and precipitation, has also been linked to increased pollution over north India, both in models (Paulot et al, 2022) and observations (Xie et al, 2023;Patnaik et al, 2024). The influence of WDs on air quality also extends to the Central Himalaya - Sundriyal et al (2018) showed that dust present in the Dokriani Glacier had come from arid regions like the Thar desert (see Fig.…”
Section: Fog Dust and Pollutionmentioning
confidence: 99%
“…Conceptually, 'ssp370pdSST' simulations represent the effect of emission changes only while 'ssp370SST' simulations represent the combined effects of climate and emission changes. The difference between 'ssp370SST' and 'ssp370pdSST' isolates and captures the climate change signal for the ssp370 pathway [3,14,33,34]. The selection of the three ESMs is based on their output of ground-level ozone concentrations, essential for calculating the human health-relevant ozone season daily maximum 8-hour mixing ratio (OSDMA8) metric.…”
Section: Datamentioning
confidence: 99%